PENGARUH HARGA KOMODITAS PANGAN DAN BENSIN TERHADAP TINGKAT INFLASI SELAMA PEMERINTAHAN JOKOWI - Sundoro, Hary Saputra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2021)
One of the economic problems in a country is controlling the inflation rate. The Government has the primary obligation to control the inflation rate accordingly. The purpose of this study is to discuss how the effect of food commodity prices and gasoline commodity prices on inflation rate movements during Jokowi's reign in the first term. The research method used is VECM with monthly analysis from October 2014 to September 2019.The results of this study find that the prices of all food commodities and gasoline commodities have a positive effect on the inflation rate. In addition, the movement of the inflation rate is most dominantly influenced by inflation itself, in other words, the most appropriate monetary policy in controlling the inflation rate. The implication of this research is that the prices of food and gasoline commodities must be controlled considering the inflation rate moves in line with the prices of these two commodities. The government can control the inflation rate by setting the reference interest accordingly because monetary policy has the most dominant influence on the inflation rate.